Antihypertensive medication and outcome in patients with COVID-19 compared to non-COVID respiratory infections. (14th October 2021) - Blum, S; Lampart, M; Zhou, Q; Mueller, C; Osswald, S; Kuster, G M; Twerenbold, R
Abstract: Background: Recent reports suggested no adverse effects of antihypertensive medication including inhibitors of the renin-angiotensin system on outcome of patients with coronavirus disease 19 (COVID-19). However, most of these studies lack adequate control groups, and regional and socio-economic differences may additionally affect clinical course and outcome of COVID-19. Methods: In the prospective observational cohort COrona VIrus surviVAl (COVIVA) study at our university hospital, we consecutively enrolled patients presenting to the emergency department with symptoms suggestive of COVID-19 between March and June 2020. Patients tested positive for COVID-19 (cases) were compared with patients tested negative, who had a respiratory infection (respiratory control). Primary outcome measure was the composite of ICU admission, 3'-day mortality or rehospitalization for respiratory symptoms. Results: The final analysis consisted of 191 patients with COVID-19 and 323 respiratory controls. Sixty cases (31.4%) and 87 (26.9%) respiratory control patients were on ACE inhibitors (ACE-I) or angiotensin II receptor blockers (ARB). In unadjusted models the hazard ratio [95% CI] for the composite outcome for patients on ACE-I/ARBs was 2.36 [1.34; 4.16], p=0.003 and 2.05 [1.03; 4.09], p=0.04 among patients with COVID-19 and respiratory controls, respectively. The corresponding multivariable adjusted HRs were 1.32 [0.68; 2.55], p=0.41 and 1.20 [0.58; 2.48], p=0.62. Furthermore, we did not observe an increased risk for the outcome when assessing ACE-Is and ARBs separately or other antihypertensive agents, both in COVID-19 patients and respiratory controls (Table). Conclusions: In a Swiss cohort of patients with COVID-19 or non-COVID respiratory controls treatment with ACE-I/ARBs or other antihypertensive medication was not associated with adverse events after accounting for comorbidities and risk factors. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Foundation for Cardiovascular Research Basel (FCVR Basel)Swiss Heart Foundation